Explaining the economic and environmental effects of quality of life on the retention of population in rural residences - Goli, Nahid (2020)
The objective of this study was to explaining the economic and environmental effects of quality of life on the retention of population in rural residences. This shows an applied research, and in terms of nature and methods, it is considered as a descriptive-analytical one. For the purpose of data collection, field studies and library studies have been conducted. To this end, an index questionnaire based on the Likert Scale was prepared and randomly distributed among the villagers. The population of the study includes 2570 individuals; however, using the Cochran’s formula, the sample size of the study was determined as 356 individuals. The collected questionnaires have been analyzed through descriptive statistics, T-test and, multivariate regression. Results show that structural equations, with a value of over 0.05 and t-statistic of 1.072, the effect of the financial aspect of life quality on retention of population is recorded. In addition, the results have also manifested that the environmental aspect of quality of life is also effective on the former with a value of 0.05 and t-statistic of 2.017, which is higher than the critical value of 1.96. Finally, it can be concluded that the environmental aspect of life-quality is significantly effective on retention of population in rural residences; however, considering the obtained path coefficient of 0.208, it is concluded that the economic aspect of life quality is not of any known significant effects on retention of population in rural areas.